EFEKTIVITAS IMPLEMENTASI SISTEM INFORMASI MANAJEMEN DAERAH (SIMDA) KEUANGAN CLOUD PADA PEMERINTAH KABUPATEN JEMBER - Sugiyantari, Diana; Titisari, Purnamie; Sumani, Sumani (BISMA: Jurnal Bisnis dan Manajemen, 2018)
Abstract: The demand on performance improvement, including financial performance, requires local government to utilize advanced information technology. The Government of Jember Regency tries to improve the financial management quality by applying a computer application named Regional Financial Management Information System or called as Finance SIMDA. SIMDA application develops in line with the latest information technology, namely cloud computing. Since March 18th, 2015, the Government of Jember has implemented cloud-based SIMDA called Cloud Finance SIMDA. The application of Cloud SIMDA is resulting in a more practical, effective, and efficient financial management. The change from the old system to the new one needs to be analyzed to examine the system effectiveness as it is expected to positively affect the increase of performance, information, economy, control, efficiency, and service or often called as PIECES (Performance, Information, Economic, Control, Efficiency, and Services) variables. This research aims to analyze the effectiveness of Finance SIMDA implementation, before and after using the cloud computing technology, with PIECES variables. This is a quantitative research with survey method. The results show that there is a difference in the effectiveness of the implementation before and after the application of cloud-based Finance SIMDA as seen from the PIECES variables. Keywords: Finance SIMDA, Effectiveness, PIECES Variables.